Antitumor progression potential of morusin suppressing STAT3 and NFκB in human hepatoma SK-Hep1 cells. Issue 2 (22nd January 2015) - Lin, Wea-Lung; Lai, Deng-Yu; Lee, Yean-Jang; Chen, Nai-Fang; Tseng, Tsui-Hwa
Graphical abstract: Highlights: Morusin suppressed cell-matrix adhesion and cell motility in SK-Hep1Cells. Morusin also increased the expression of E-cadhesion. Morusin reduced the activity of matrix metalloproteinase -2 and 9. The mechanism is through suppressing the STAT3 and NFκB signaling pathways. Morusin decreased the lung colonization of the SK-Hep1 cells in the nude mice. Abstract: Morusin is a prenylated flavonoid that has been isolated from the root bark of the mulberry tree ( Morus species, Moraceae ), a Chinese traditional medicine. It has been synthesized by our laboratory from commercially available phloroglucinol, and has demonstrated to possess antitumor effects of cell lines including A549, MCF-7, and MDA-MB-231. In this study, at non-cytotoxic concentrations, morusin altered invasive morphology and suppressed cell-matrix adhesion, cell motility and cell invasion in SK-Hep1 cells. Morusin also increased the expression of E-cadherin, an epithelial cell junction protein, decreased the expression of vimentin, a mesecnchymal marker, and α2-, α6-, β1- integrin, which regulated cancer attachment and migration. In addition, morusin reduced the activity of matrix metalloproteinase-2 and 9 (MMP-2 and MMP-9), which were involved in extracellular matrix (ECM) degradation and promoting cancer cell invasion. Furthermore, morusin suppressed the signal transducer and activator of transcription 3 (STAT3) and nuclear factor-κB (NFκB) signaling pathways, which modulate the protein expression involved in the invasion process. Finally, morusin decreased the lung colonization of the SK-Hep1 cells in the nude mice. These results indicate morusin possesses antitumor progression potential through suppressing STAT3 and NFκB.